Methodological considerations and implications for appetite and feeding behaviour research in PKU; Current knowledge, practical application and future perspectives - Ben Green (Rare)
Appetite and the regulation of feeding behaviour are sophisticated processes. Regulated through homeostatic and non-homeostatic influences, appetite-related peptides and external cues existing in the physical environment work synergistically to maintain energy homeostasis. Phenylketonuria (PKU) is a rare disorder impacting phenylalanine metabolism. The disrupted breakdown of phenylalanine into tyrosine and its metabolites may impact the mechanisms controlling appetite and feeding behaviour compared to non-PKU counterparts. This may, in part, relate to consumption of L-amino acid protein substitutes and specialist low-protein foods which are integral adjuncts to the dietary management of PKU. While adequate energy intake is an important factor for maintaining satisfactory blood phenylalanine concentrations, appetite and feeding behaviour should, therefore, represent an integral consideration for PKU but is currently understudied. Only a handful of studies have evaluated appetite and feeding behaviour in PKU. The most appropriate methodological approaches of these studies however were not employed. This manuscript, therefore, reviews the purported mechanisms controlling appetite and feeding behaviour and from a PKU perspective provides readers with sound study design proposals and justification. Though one method will not answer all research questions, this manuscript may help researchers and practitioners make informed decisions about what tools and methodological approaches will provide the most meaningful outcomes. The manuscript concludes with suggestions for future research directions. Though the evidence concerning appetite and feeding behaviour in PKU remains equivocal at present, early data appears to indicate that protein substitutes with glycomacropeptide facilitate metabolic control and improve appetite-relate peptide regulation and therefore satiety signalling in PKU.